2020
DOI: 10.7251/agreng2002077p
|View full text |Cite
|
Sign up to set email alerts
|

The Estimation of Heat and Drought Tolerance Maize Lines Using Dna Markers

Abstract: The main factor which causes to decrease maize grain yield is drought. In most regions where maize is grown, the water stress during the growing period is caused by both lack of soil moisture and high air temperature. The purposes of our study were the estimation and selection of maize lines for drought and heat tolerance based on DNA markers and determination of the correlation between CAPS markers and plant ability to resist the water stress. As the result of study, the significant differences were found bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Prysiazhniuk et al (2018) found the two genes dhn1 and rsp41to be related with drought resistance in maize lines. Prysiazhniuk et al (2018) suggested that these lines can be used further for development of drought-resistant maize hybrids. As in present case, about 51 plants for LM23 and 89 for LM24 were found in BC 3 F 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Prysiazhniuk et al (2018) found the two genes dhn1 and rsp41to be related with drought resistance in maize lines. Prysiazhniuk et al (2018) suggested that these lines can be used further for development of drought-resistant maize hybrids. As in present case, about 51 plants for LM23 and 89 for LM24 were found in BC 3 F 1 .…”
Section: Discussionmentioning
confidence: 99%